Climatic and microclimatic conditions of vanilla (Vanilla planifolia Jacks. ex Andrews) production systems in Mexico - Parada-Molina, Paulo César (2022)
Introduction. Vanilla is grown in agroecosystems under varying management intensities, with particular environmental characteristics that could be unfavorable for the orchid. Atmospheric conditions are important due to climate change. Objective. To characterize the climatic and microclimatic conditions of three vanilla (Vanilla planifolia Jacks. ex Andrews) production systems. Materials and methods. The study was carried out in three vanilla production systems located in Veracruz and Oaxaca, Mexico. Three management intensities were used: a) acahual, under the shade of various tree species; (b) monoculture, interspersed with an arboreal species; and (c) shade mesh (with artificial shade). One year of monitoring was carried out (December-2020 to November-2021), which included four climatic seasons, two cold and two warm. Climatic variables (region) and microclimatic (plot) variables were measured: temperature (T), relative humidity (HR), and photosynthetically active radiation (PAR, only in the microclimate), with automated stations; in addition, the vapor pressure deficit (VPD) was calculated. Results. On a daily scale, climatic conditions as microclimatic in the acahual were more favorable for vanilla cultivation in the four seasons evaluated; the monoculture and the shade mesh experienced humidity and temperature conditions outside the agroclimatic requirements of vanilla, mainly in March-May (MAM), with Tmax >32 ¡C and RH <80 %. On an hourly scale, the warmest and driest conditions were in monoculture and shade mesh in December-February (DEF) and MAM; while in June-August (JJA) and September-November (SON) in acahual and shade mesh; VPD (>2 kPa) indicated longer periods of water stress in these systems. Conclusions. The monoculture and the shade mesh presented unfavorable humidity and temperature conditions for vanilla, with more periods of water stress. The acahual presented the most convenient climatic and microclimatic conditions for the cultivation of vanilla.